Cyperus (Cyperus esculentus L.): A Review of Its Compositions, Medical Efficacy, Antibacterial Activity and Allelopathic Potentials - Zhang, Shengai; Li, Peizhi; Wei, Zunmiao; Cheng, Yan; Liu, Jiayao; Yang, Yanmin; Wang, Yuyan; Mu, Zhongsheng (Plants (Basel), 2022)
Cyperus (Cyperus esculentus L.) is an edible perennial grass-like plant, which propagates exclusively with underground tubers. Its tubers are rich in starch (20–30%), fat (25–35%), sugar (10–20%), protein (10–15%) and dietary fiber (8–9%). In addition, the tubers also contain alkaloids, organic acids, vitamins (C and E), steroids, terpenoids and other active components. The contents of oleic acid and linoleic acid in Cyperus oil are very high, which have important medicinal value and health-promoting properties. Most of the extracts from the tubers, stems and leaves of Cyperus have allelopathic potential and antibacterial, antioxidant and insecticidal activities. In recent years, the planting area of Cyperus has increased significantly all over the world, especially in China and some other countries. This paper presents the current status of Cyperus and the recent trend in research in this area. Published reports on its nutritional contents, active ingredients, medicinal efficacy, antibacterial activity and allelopathic potential were also reviewed.